BAITUL MAL WAT TAMWIL (BMT) STRATEGI IN THE ERA OF ECONOMIC DISRUPTION - Fatriansyah, Alif Ilham Akbar; Junaedi, Wahyu; Fadhlihi, Andueriganta; Anggrayni, Lilly (Journal of Finance, Economics and Business, 2023)
This study aims to find new strategies for BMT in an era of economic disruption. BMT as a sharia microfinance institution faces challenges from digital technology-based financial institutions (Financial Technology / FinTech) whose market share is increasing, and have the opportunity to seize the market share of BMT, namely the unbankable people. The method used in this research is the literature review. This research produces three strategies that can be carried out by BMTs to be able to compete in an era of economic disruption, namely, first to strengthen the commitment of the board and members to carry out sharia contracts to strengthen institutional branding, secondly, using digital technology to facilitate services and reach unbankable segments of society, and thirdly, to encourage productive business financing according to the comparative advantages of each region in the area of BMT business activities.